2022
DOI: 10.1029/2022je007456
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Ocean Bistability on Terrestrial Exoplanets

Abstract: Cycling of carbon dioxide between the atmosphere and interior of rocky planets can stabilize global climate and enable planetary surface temperatures above freezing over geologic time. However, variations in global carbon budget and unstable feedback cycles between planetary sub‐systems may destabilize the climate of rocky exoplanets toward regimes unknown in the Solar System. Here, we perform clear‐sky atmospheric radiative transfer and surface weathering simulations to probe the stability of climate equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Radiative transfer calculations coupled to Isca's dynamics are carried out with the SOCRATES code (Edwards & Slingo 1996), using the correlated-k method to solve the planeparallel, two-stream approximated radiative transfer equation with scattering for atmospheres irradiated by a solar (G-star) spectrum. In high-instellation, low-pCO 2 simulations, we used Graham et al (2022) and found the output from the GCM stayed within 5 W m −2 of the higherresolution calculations). Rayleigh scattering is interactively calculated with coefficients included in SOCRATES for the relevant gases.…”
Section: Climate Modelmentioning
confidence: 97%
See 3 more Smart Citations
“…Radiative transfer calculations coupled to Isca's dynamics are carried out with the SOCRATES code (Edwards & Slingo 1996), using the correlated-k method to solve the planeparallel, two-stream approximated radiative transfer equation with scattering for atmospheres irradiated by a solar (G-star) spectrum. In high-instellation, low-pCO 2 simulations, we used Graham et al (2022) and found the output from the GCM stayed within 5 W m −2 of the higherresolution calculations). Rayleigh scattering is interactively calculated with coefficients included in SOCRATES for the relevant gases.…”
Section: Climate Modelmentioning
confidence: 97%
“…At somewhat lower instellations than S = 1000 W m −2 , CO 2 condensation at the surface would become a possibility at high enough pCO 2 , meaning the energetic limit on precipitation presents a pathway to reach the stable CO 2 ocean states proposed in Graham et al (2022). The mechanism of carbon cycle destabilization suggested in that study was based on the fact that CO 2 becomes a coolant at extremely high partial pressures, which also leads to a slowdown of weathering with pCO 2 accumulation but requires much higher CO 2 to initiate than the mechanism discussed here.…”
Section: Catastrophic Carbon Cycle Hysteresismentioning
confidence: 98%
See 2 more Smart Citations
“…Consequently, the instellation at which the runaway greenhouse transition occurs is aptly considered to be the inner boundary of the habitable zone (e.g., Ramirez 2018;. Its prevalent definition refers to the possibility of a sustained liquid water body on the surface of an Earth-like planet with an oxidized CO 2 /H 2 O/N 2 -rich atmosphere (Kasting et al 1993;Kopparapu et al 2013Kopparapu et al , 2014; its exact spatial location and extent may be strongly influenced by the interior and atmosphere oxidation state and resulting atmosphere composition (Pierrehumbert & Gaidos 2011;Ramirez & Kaltenegger 2017, 2018Katyal et al 2019;Graham & Pierrehumbert 2020;Graham et al 2022;Hakim et al 2023). The fundamental concept of a habitable zone dates back centuries (Newton 1846;Whewell 1858;Shapley 1953;Huang 1959), and its modern form has proven popular in the planetary literature.…”
Section: Introductionmentioning
confidence: 99%